2014
DOI: 10.1097/ccm.0000000000000218
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Injury, Early Gene Expression, and Gram-Negative Bacteremia*

Abstract: Rationale Bacteremic trauma victims have a higher risk of death than their non-bacteremic counterparts. The role that altered immunity plays in the development of bacteremia is unknown. Objective Using an existing dataset, we sought to determine if differences in early post-injury immune-related gene expression are associated with subsequent gram-negative bacteremia (GNB). Design Retrospective cohort study, a secondary analysis of the Glue Grant database. Subjects Severely injured blunt trauma patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 38 publications
3
7
0
1
Order By: Relevance
“…4 ). Remarkably, these results are in line with a very recent study in post-traumatic patients developing sepsis, which demonstrates a down-regulation of IL-1β as well as an up-regulation of IL1R2 gene expression and proposingg a suppression of innate immunity [ 25 ].…”
Section: Resultssupporting
confidence: 88%
“…4 ). Remarkably, these results are in line with a very recent study in post-traumatic patients developing sepsis, which demonstrates a down-regulation of IL-1β as well as an up-regulation of IL1R2 gene expression and proposingg a suppression of innate immunity [ 25 ].…”
Section: Resultssupporting
confidence: 88%
“…IL1-R2 is counteracting inflammation by binding IL-1beta without intracellular signaling transduction, and its gene expression has been reported earlier to be of high diagnostic usefulness for sepsis, also after trauma. [ 40 , 41 ] Similar results have been shown for inflammatory IL-18 and blocking it together with IL-1β protected animals against inflammation and shock. [ 42 ]…”
Section: Discussionsupporting
confidence: 63%
“…An analysis of leukocyte gene expression associated with post-trauma Gram-negative bacteremia in the Glue Grant dataset showed that both innate and adaptive immunity appeared to be suppressed by 96 hours postinjury. 138 These findings suggested that immunostimulants, such as interferon-gamma, in patients with decreased immune gene expression, may be a promising therapeutic approach. GM-CSF was tested in small trauma populations and shown to counteract trauma-induced monocyte function depression while IFN-γ had the capacity to enhance HLA-DR on B and T lymphocytes.…”
Section: Interventionsmentioning
confidence: 99%